Rapid Sensitive Assay for Interferons Based on the Inhibition of MM Virus Nucleic Acid Synthesis - Allen, Patton T. (1970)
A method for assaying mouse interferon based on the inhibition of viral ribonucleic acid (RNA) synthesis was devised. The amount of MM virus and RNA synthesized in interferon-treated L-cell cultures was determined by measuring the amount of (3)H-uridine converted into a trichloroacetic acid-insoluble form after treatment of the infected cultures with 2.5 μg of actinomycin D per ml. The amount of RNA synthesized was inversely related to the concentration of interferon used for treatment. A linear dose-response regression curve was obtained by plotting the log of the amount of RNA made, expressed as a percentage of the control, versus the log of the reciprocal of the interferon dilution. A unit of interferon was defined as that concentration which inhibited nucleic acid synthesis by 50% (INAS(50)). The concentration of mouse interferon could be determined within 24 hr. This assay method, on the average, was approximately half as sensitive as the method which measured the 50% reduction of MM virus plaque number (PDD(50)-MM method), but was, on the average, almost 1.7 times as sensitive as the PDD(50)-VSV method. It averaged approximately 20 times the sensitivity of the methods which used as end points the 70% reduction in yield of MM virus or the complete inhibition of cytopathic effect by MM virus. The reproducibility of the INAS(50) technique was tested in two ways. (i) Four independent assays of an interferon specimen were performed with replicate cultures. The standard deviation was 11.2% of the mean titer. (ii) On different dates, one interferon specimen was assayed seven times and another was assayed four times. The standard deviations were 21.5 and 26.6% of the respective mean titers.